Water‐Insensitive Electron Transport and Photoactive Layers for Improved Underwater Stability of Organic Photovoltaics. (5th July 2022) - Lin, Chieh‐Ting; Hsieh, Cheng‐Tien; Macdonald, Thomas J.; Chang, Jia‐Fu; Lin, Po‐Chen; Cha, Hyojung; Steier, Ludmilla; Wadsworth, Andrew; McCulloch, Iain; Chueh, Chu‐Chen; Durrant, James R
Abstract: Water ingress is one of the major environmental stresses to cause the degradation of device performance in organic photovoltaic (OPVs) and is one of the major barriers impeding their commercialization. This work demonstrates that combining the use of a nanoparticle titanium dioxide (np‐TiO2 ) electron transporting layer (ETL) and an all‐polymer bulk heterojunction (BHJ) photoactive layer can endow the derived OPV with a much better water resistivity than the commonly employed zinc oxide (ZnO) ETL or polymer:small molecule BHJ blends. Polymer donors/acceptors are first shown to possess better water‐immersion than the small molecule counterparts. Hence, the all‐polymer blend exhibits the lowest absorbance losses after water immersion among the studied BHJ systems. Furthermore, the result reveals that tailoring the structure of the TiO2 ETL from planar to nanoparticles effectively strengthens the adhesion at the ETL/BHJ interface to prevent physical delamination. Finally, the np‐TiO2 /all‐polymer blend (half‐cell) is demonstrated to have superior stability under water immersion, i.e., unchanged morphology and charge carrier transfer, as well as no efficiency changes in the complete cells. This work demonstrates the great potential of the all‐polymer blends and np‐TiO2 ETL for improving the durability of unencapsulated OPVs under high humidity environments and even water immersion. Abstract : The underwater stability of organic photovoltaics is successfully enhanced through a systematic water‐insensitive engineering of organic photoactive layers and electron‐transporting layers. The all‐polymer blend film exhibits the lowest absorbance losses after water immersion among studied bulk‐heterojunction systems. Substituting ZnO with TiO2 can achieve a more stable morphology after water immersion, and tailoring the nanostructure of TiO2 from planar to nanoparticle can better strengthen its adhesion with the all‐polymer blend to prevent physical delamination.